Key factors of competitive tourist destinations: A study in San Carlos, Antioquia, Colombia - Marín-Idárraga, Diego Armando (2023)
The purpose of this research is to identify the key factors explaining the competitiveness of a tourist destination, namely San Carlos in Antioquia, Colombia. The main results of the exploratory and confirmatory factor analysis show that this Colombian region will fully materialize its tourism competitive potential if it develops more integrated support action plans, supports the effective exploitation of inherent resources, and promotes a better management of the destination. These results have important implications for the design of public tourism policy, both in the region and in other territories.